Reintroduction of excluded food triggers as a crucial step in managing patients with food allergies - A. A. Galimova; S. G. Makarova (Association of Paediatric Allergists and Immunologists of Russia (APAIR), 2024)
Introduction. Despite active research into the mechanisms of food allergies (FA), the main approach to managing patients with this condition remains the complete exclusion of causative allergens from the diet for a certain period. At the same time, the question of timely reintroduction of excluded food triggers into the diet is frequently raised, which is important both for maintaining oral tolerance and reducing the negative effects of long-term elimination diets, such as nutritional and eating behavior disorders, as well as financial burdens on families. However, clear recommendations on the reintroduction of previously excluded foods have not existed until recently. Regarding cow's milk protein allergy (CMPA), such recommendations were provided in 2023 in the consensus document of the World Allergy Organization (WAO) - DRACMA.Aim. The aim of this review is to present current approaches to the reintroduction of food allergens into the diets of patients with food allergies and to evaluate various reintroduction protocols, including those used for cow's milk protein allergy (CMPA).Material and methods. This review provides a concise summary of current approaches to reintroducing food allergens into the diet, covering both IgE-mediated and non-IgE-mediated forms of food allergy. The advantages of different patient management protocols are discussed, with special attention given to CMPA as one of the most common manifestations of FA in children.Results. An analysis of modern approaches has demonstrated that modern recommendations regarding the reintroduction of allergens, including those presented in the document of the World Allergological Organization - DRACMA for allergy to cow's milk proteins, allow for a more personalized and safe approach to the reintroduction of allergens, which helps reduce risks and maintain food tolerance.Conclusions. The introduction of new guidelines for the reintroduction of food allergens is an important step in managing patients with food allergies. These recommendations provide a more personalized approach to treating food-allergic patients, including those with cow's milk protein allergy, reducing the risks associated with reintroducing allergens into the diet. They also help to mitigate the negative effects of elimination diets and maintain oral tolerance in patients, which is particularly important for children with FA.